An X chromosome-wide association analysis identifies variants in GPR174 as a risk factor for Graves' disease. Issue 7 (10th May 2013) - Chu, Xun; Shen, Min; Xie, Fang; Miao, Xiao-Jing; Shou, Wei-Hua; Liu, Lin; Yang, Peng-Peng; Bai, Ya-Nan; Zhang, Kai-Yue; Yang, Lin; Hua, Qi; Liu, Wen-Dong; et al.
Abstract : Background: Graves' disease is a female preponderant autoimmune illness and the contribution of the X chromosome to its risk has long been appreciated. However, no X-linked susceptibility loci have been indentified from recent genome-wide association studies (GWAS). Methods: We re-examined the X chromosome data from our recent GWAS for Graves' disease by including males that were previously excluded from the X chromosome analyses. The data were analysed using logistic regression analysis including sex as a covariate, and an additive method assuming X chromosome inactivation, implemented in snpMatrix. Results: A cluster of single nucleotide polymorphism (SNPs) at Xq21.1 was found showing association with genome-wide significance, among which rs3827440 was a non-synonymous SNP of GPR174 (Plogistic regression = 9.52×10 −8 ; PsnpMatrix =4.60×10 −9 ; OR=1.76, 95% CI 1.45 to 2.13). The association was reproduced in an independent sample collection set including 4564 Graves' disease cases and 3968 sex matched controls (combined Plogistic regression =5.53×10 −21 ; combined PsnpMatrix =4.26×10 −22 ; OR=1.69, 95% CI 1.53 to 1.86). Notably, GPR174 was widely expressed in immune related tissues and rs3827440 genotypes were associated with distinct mRNA levels (p=0.002). GPR174 did not show sex biased gene expression in our expression analysis. Resequencing study suggested the contribution of some rare variants in the GPR174 gene region to disease risk with a collapsing p value of 1.16×10 −3 . Conclusions: The finding of an X-linked risk locus for Graves' disease expands our understanding of the role of the X chromosome in disease susceptibility.